2001
DOI: 10.1117/12.436905
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of electron beam stabilization of 193-nm photoresists

Abstract: 193nm lithography is a promising candidate for the fabrication of microelectronic devices at the l3Onm design rule and below. With smaller feature sizes, below l3Onm, reduced resist thickness is essential because of the pattern collapse issues at high aspect ratios and the limited depth of focus with 193nm lithography tools. However, ArF resists have shown problems with etch selectivity, especially with the thin resist layers necessary. Additionally, pattern slimming during CD-SEM measurement, due to the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…6). Kim et al 4 have reported that resists based on poly(norbornene derivative/malefic anhydride) or "COMA" type shrink more (30 %) compared to methacrylate (18 %) using the same standard ebeam curing process as the current study. Although a direct comparison is not possible as the acid sensitive groups are different, it is reasonable to assume that the hybrid type would have shrinkage between that of COMA and pure methacrylate.…”
Section: Effect Of A-beam Curing On the Film Shrinkagementioning
confidence: 79%
See 4 more Smart Citations
“…6). Kim et al 4 have reported that resists based on poly(norbornene derivative/malefic anhydride) or "COMA" type shrink more (30 %) compared to methacrylate (18 %) using the same standard ebeam curing process as the current study. Although a direct comparison is not possible as the acid sensitive groups are different, it is reasonable to assume that the hybrid type would have shrinkage between that of COMA and pure methacrylate.…”
Section: Effect Of A-beam Curing On the Film Shrinkagementioning
confidence: 79%
“…It has been reported that 193nm resists of the kinds shown in Scheme 1 undergo a loss of carbonyl groups upon a-beam curing and moderate changes in the C-H, C-H2 and C-H3 bonds in the 3000-2800 cm l region [3][4]. In this study, the influence of three different processes, viz., standard, LT and ESC, on the level of carbonyl loss in the FTIR were observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations